Multivariate intralocus sexual conflict in seed beetles. (22nd October 2014) - Berger, David; Berg, Elena C.; Widegren, William; Arnqvist, Göran; Maklakov, Alexei A.
<x xml:space="preserve">Abstract</x> Intralocus sexual conflict (IaSC) is pervasive because males and females experience differences in selection but share much of the same genome. Traits with integrated genetic architecture should be reservoirs of sexually antagonistic genetic variation for fitness, but explorations of multivariate IaSC are scarce. Previously, we showed that upward artificial selection on male life span decreased male fitness but increased female fitness compared with downward selection in the seed beetle Callosobruchus maculatus. Here, we use these selection lines to investigate sex‐specific evolution of four functionally integrated traits (metabolic rate, locomotor activity, body mass, and life span) that collectively define a sexually dimorphic life‐history syndrome in many species. Male‐limited selection for short life span led to correlated evolution in females toward a more male‐like multivariate phenotype. Conversely, males selected for long life span became more female‐like, implying that IaSC results from genetic integration of this suite of traits. However, while life span, metabolism, and body mass showed correlated evolution in the sexes, activity did not evolve in males but, surprisingly, did so in females. This led to sexual monomorphism in locomotor activity in short‐life lines associated with detrimental effects in females. Our results thus support the general tenet that widespread pleiotropy generates IaSC despite sex‐specific genetic architecture.